The effects of core formation on the Pb- and Tl- isotopic composition of the silicate Earth - Wood, B; Nielsen, S; Rehkamper, M; Halliday, A (2008)
We have performed metal-silicate partitioning experiments at 2 GPa and 1650-2180 °C to investigate the behaviour of Pb and Tl during terrestrial core formation. The aim was to test the hypothesis that metal core formation followed by late sulphide addition to the core resulted in the concentrations and isotopic compositions of Pb and Tl in the silicate Earth. We investigated DPbmet/sil and DTLmet/sil as functions of the sulphur content of the metal and measured the equilibrium Tl isotope fractionation between the coexisting phases. Lead is moderately siderophile under the likely conditions (initially reducing [Wade, J., Wood, B.J., Core formation and the oxidation state of the Earth, Earth Planet. Sci. Lett. 236(2005) 78-95.]) of core segregation on Earth so that the μ(238U/204Pb) of the bulk silicate Earth should have increased by a factor of 6.5 (DPb ∼ 13) as the core separated. In the case of Tl, core segregation should have reduced the Tl concentration of the BSE by about 50%. Neither the Pb nor Tl isotopic compositions of the bulk silicate Earth can, however, be completely explained by S-free iron core formation. Thallium isotopes were found not to be significantly fractionated by metal or sulphide separation from silicate. Addition of sulphur to the metal greatly increases metal-silicate partition coefficients for both Pb and Tl. DPbmet/sil increases by a factor of 15 and DTLmet/sil by a factor of 45 as S increases from 0 to 35% in the metal phase. This means that extraction of sulphide from a molten mantle would result in DPbsulph/sil of ∼ 40 and DTLsulph/sil of ∼ 60. We used the latter results to calculate the effects of late sulphide extraction on the Pb and Tl isotopic compositions of the silicate Earth. For a bulk Earth with μ of 0.7 addition of 1.6% sulphide to the core 100-140 Myr after the beginning of the solar system is sufficient to displace the Pb-isotopic composition of the silicate Earth into the region indicated by estimates in the literature. The Tl concentration and e{open}205Tl of bulk silicate Earth are also consistent with this extent of sulphide addition. Raising μ of the Earth reduces the amount of sulphide addition to the core needed to satisfy the Pb and Tl isotopic constraints but for values of μ above 0.9 (< 0.65% sulphide) the sulphide has insufficient effect. Separation of sulphide from a mixture of silicate crystals and melt would, however, because of the incompatible nature of Pb and Tl amplify the sulphide effect. We show that, for initial μ of 0.7, as little as 0.1% sulphide extraction (at 150-200 Myr) from a mixture of 91% crystals and 9% melt would be sufficient to displace the isotopic compositions of Pb and Tl of the BSE to the required values. Late volatile loss of Pb and Tl is, therefore, not required by the partitioning and currently available isotopic data. © 2008 Elsevier B.V. All rights reserved.